HUBUNGAN DUKUNGAN KELUARGA DENGAN KEMANDIRIAN LANSIA DALAM AKTIVITAS SEHARI HARI - Sumiati Sumiati (Jurnal Medika : Karya Ilmiah Kesehatan, 2019)
Background : Continuation of age is someone because of his age experiencing biological, physical, psychological, and social changes. Changes that occur due to age which further reduce one's independence, this means that the elderly who are weak cannot take care of themselves. To fulfill the ADL, the elderly need a family role to increase their independence. Family support is one type of social support. Mutual interactions between individuals or family members can lead to a relationship of dependence on each other. Independence means no supervision, direction, or active assistance from others. A person who refuses to perform a function is deemed not to function even though he is actually capable. Objective : To determine the relationship between family support and the independence of the elderly in daily activities in the Karang Asam Samarinda HealthCenter. Method: This study uses a cross sectional design. The sample is all the elderly who are registered in the Asam samarinda coral health center. The variable observed is family support with the independence of the elderly. With a population of 110 people and a sample of 52 people. Data is collected using a questionnaire. Data were analyzed by descriptive correlation with significant p <0.05. Results : Research shows that there is a significant relationship between family support and the independence of the elderly from the Chi Square results obtained p value = 0,000 thus p value is smaller than alpha 0.05 then Ho is rejected, it can be concluded that there is a significant relationship between family support and independence of the elderly in daily activities in the Karang Asam Samarinda Health Center.Conclusion : Family support is needed by the elderly, so that the elderly are expected to be able to carry out daily activities independently.